WORKSHOP IMPLEMENTASI DEEP LEARNING MELALUI PROJECT BASED LEARNING UNTUK MENINGKATKAN KOMPETENSI GURU DI DESA CISAAT, KABUPATEN SUBANG - Etin Solihatin; Raharjo Raharjo; Yuyus Kardiman; Roby Ibnu Syarifain; Ricky Rasyid (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
The transformation of learning paradigms in the digital era requires teachers to possess pedagogical competencies that support student-centered, contextual, and twenty-first-century learning. However, the needs assessment conducted in Cisaat Village, Ciater District, Subang Regency indicated that teachers still required greater understanding of the implementation of the Deep Learning approach through the Project-Based Learning (PjBL) model. This community service program aimed to strengthen teachers' understanding of the concepts and implementation of Deep Learning through Project-Based Learning to support the improvement of instructional quality. The program was conducted through a participatory workshop involving 12 teachers from four educational institutions in Cisaat Village. Learning activities consisted of interactive lectures, discussions, question-and-answer sessions, and Focus Group Discussions (FGDs). Program evaluation was carried out using a participant feedback questionnaire, and the data were analyzed descriptively using percentage analysis. The evaluation results showed that all participants (100%) agreed that the workshop materials were aligned with the objectives of the program. Furthermore, 92.3% of participants rated the clarity of the presenters as excellent, while 84.6% considered the materials highly relevant to their professional needs and supported by adequate learning resources. Participants also provided positive evaluations regarding the effectiveness of the instructional media, the learning environment, and the overall contribution of the workshop in strengthening their understanding of Deep Learning through Project-Based Learning. The program contributed to strengthening teachers' pedagogical capacity while fostering sustainable collaboration among the university, local government, and educational institutions to improve the quality of teaching and learning.